Uma proposta para a inserção do tempo de uso dos equipamentos no aplicativo APR e estudos avaliativos de casos reais de PID´S - Gadenz, Fernando (2010)
A very controversial issue that assumes increasing importance in the national scenario is related to the well area known as Refunding Request for Damages. This subject, amongst other aspects, aims at providing means to support the necessary answer to the consumers when a equipment damage is claimed due to a occurrence in the electrical network. With this in mind, the main idea consists in establishing a correct relationship between power system distribution or transmission phenomena with a given required demand for refunding. In this way, the conventional procedures actually in practice are quite empirical and the search for computational means to provide the required answer appears as an attractive scientific and technique base approach. Using this approach it is believed that a more consistent and impartial method would be of great help to accomplish the focused matter. Within this context, this dissertation aims to contribute in two specific topics: the first is associated to a methodology to cope with the equipment time of use and its insertion in the so called APR software. The second target goes towards the investigation of 25 cases of real refunding requests occurred at the Centrais Eletricas Matogrossenses CEMAT so as to provide a first step towards the validation procedure of the overall procedures.